PELATIHAN KEWIRAUSAHAAN BERBASIS DIGITAL MARKETING BAGI PELAKU UMKM KULINER - Amaliyah Ariany Arifin (PT. CASA CENDEKIA MEDIA, 2025)
This community service project aimed to enhance digital entrepreneurship skills among culinary MSME actors in Tangerang Regency through Digital Marketing training. Employing a participatory action research approach, 30 participants were purposively selected from active culinary business owners. The training combined workshops, practical sessions, and mentoring on social media management, content creation, and online branding. Data were collected via observations, pre- and post-tests, and in-depth interviews. Quantitative analysis using descriptive statistics and paired t-test indicated a significant improvement in participants’ understanding and application of digital marketing (p < 0.05). Qualitative findings showed increased confidence in using digital tools, producing creative content, and promoting products online. Overall, the program effectively improved digital literacy and marketing competence, empowering MSMEs to adopt a digital mindset, expand their market reach, and enhance business competitiveness in the digital economy.